Being regional': an analysis of the conceptualisation, operations and embeddedness of regional non-governmental organisations responding to HIV and AIDS in Southern Africa - Mushonga, Allan (Rhodes University, Faculty of Humanities, Department of Sociology, 2020)
This thesis offers an original sociological analysis of regional Non-Governmental Organisations (RNGOs) responding to the HIV epidemic in the Southern African Development Community (SADC) in respect of their emergence, constitution, role, function, embeddedness, accountability and practice of being regional in the HIV response. In doing so, it offers propositions on the conceptualisation of RNGOs and the concept being regional in clarifying regional HIV programming in the context of regionalisation. It also highlights the nexus between regional HIV work, and country and global HIV governance and programming as components of the global architecture of development regime under the tutelage of the United Nations as influenced by the dominant powers. The analysis is based on a hybrid of social systems, actor systems dynamics, institutional and network theoretical analytical frameworks. A triangulation of these frameworks provides a comprehensive grounding on which it is possible to identify and analyse RNGOs as social systems, institutions, actors and nodes that constitute part of the global architecture of the HIV response. This also facilitates the conceptualisation of being regional as both a programmatic typology and state of existence of RNGOs, thus locating these regional actors in the framework of the global HIV governance and programming. It locates them in the resultant web of social relations connecting various development agents in hierarchical and institutionalised structures constructed around HIV governance and responses. Social embeddedness and hence accountability of RNGOs is thus presented as determined by this complex context. Based on an extensive use of organisational documents as well as key informant interviews, the thesis reveals the dominance of funding organisations in determining regional and national HIV programme design and content as well as structuring the organisational practices of RNGOs and other development agents in the HIV response. Because of the demands by donors for accountability on the part of RNGOs for funds received, upward accountability becomes a major preoccupation of RNGOs and becomes privileged compared to downward accountability to their programme beneficiaries. However, RNGOs still enact agency in seeking to manoeuvre their way through the worldwide development system in order to advance the HIV response while also ensuring their own organisational sustainability.
Keywords: AIDS (Disease) -- South Africa -- Finance; Non-governmental organizations -- South Africa